Arizona - Somervill, Barbara A (New York Children's Press, 2009)
This introduction to Arizona bursts with fascinating facts, up-to-date statistics, glorious full-color photographs, and unusual lists. It features charts, graphs, maps, timelines, traceable state symbols, a travel guide, a project room packed with ideas for classroom assignments, a biographical dictionary, weird laws, and content-area vocabulary words
Land : find out about deserts, dust devils, cactus, and rattlesnakes -- First people : learn about the Mogollon, Hohokam, and Anasazi -- Exploration and settlement : follow the Spaniards as they come upon the Grand Canyon -- Growth and change : read about silver, the Wild West, and the Apaches -- More modern times : see how statehood tamed Arizona -- People : find out about Native Americans, modern cowboys, and hotter-than-hot salsa -- Government : meet the Fab Five and learn how Arizona's laws are made -- Economy : discover how silver, copper, and tourism boost Arizona's economy -- Travel guide : get out your guide to trekking deserts and travel from the Four Corners to the Sonoran Desert -- Projects -- Timeline -- Glossary -- Fast facts -- Biographical dictionary
Includes bibliographical references (p. 137-138) and index
Hurg
5
Keywords: Arizona -- Juvenile literature; Arizona